Can leader-member exchange social comparison elicit uncivil employee behavior? The buffering role of aggression-preventive supervisor behavior. Issue 3 (22nd December 2020) - Sharma, Dheeraj; Mishra, Madhurima; Pandey, Shivendra Kumar; Ghosh, Koustab
Abstract : Purpose: This study aims to examine the role of leader-member exchange social comparison (LMXSC) perceptions in triggering the instigation of uncivil behavior in the workplace. This study also explores the intervening role of envy and the buffering role of aggression-preventive supervisor behavior within the proposed relationship. Design/methodology/approach: Data were collected in two phases separated by an interval of four weeks. The final sample consisted of 224 full-time white-collar employees working in five large pharmaceutical manufacturing organizations in India. Findings: The findings indicate that employees' subjective perceptions of being involved in poorer-quality LMX relationships than their workgroup members generate envy, which, in turn, evokes them to instigate uncivil behaviors onto those higher-LMX counterparts. The indirect effect of LMX social comparison on instigated workplace incivility through envy gets attenuated when supervisors engage in aggression-preventive behavior. Practical implications: To protect organizations from the financial and productivity losses associated with incivility, supervisors are encouraged to exhibit aggression-preventive behavior if they form differentiated exchange relationships with the subordinates in their teams. Supervisors are further advised to avoid the altogether neglect of lower-LMX subordinates as doing so may give rise to negative emotions (envy) and behavior (incivility) among them. Originality/value: This study expands the limited body of knowledge on the antecedents of uncivil employee behavior in the workplace. Specifically, it unveils that incivility toward coworkers may be stemming from unfavorable LMX social comparisons and ensuing negative emotions such as envy. It also offers insights on reducing uncivil behavior by highlighting that the impact of LMXSC and envy on incivility instigation gets buffered in the presence of aggression-preventive supervisor behavior.